Aspectos autorais nas animações de Hayao Miyazaki - NOVAES, Viktor Danko Perkusich (2018)
This dissertation verifies in the work of Hayao Miyazaki, the aspects of its production that make possible to recognize it like director-author, its subjects and feminine characters. Each film is analyzed from a single perspective. Subjects such as religion, folklore, narrative themes, adaptation problems and issues related to the director, their beliefs, political and social views were taken into consideration. The analysis will be based on nine full-length feature films produced from the foundation of Studio Ghibli in 1985. Tenkû no shiro Rapyuta (The Castle in the Sky) 1986, Tonari no Totoro (My Neighbor Totoro) 1988, Majo no takkyûbin (O Kiki's Delivery Service 1989), Kurenai no buta (Porco Rosso) 1992, Mononoke-hime (Princess Mononoke) 1997, Sen to Chihiro no kamikakushi (Spirited Away) 2001, Hauru no ugoku shiro (Howl’s Moving Castle) 2004, Gake no ue no Ponyo (Ponyo on the Cliff by the Sea) 2008 and Kaze Tachinu (The Wind Rises) 2013.